Analysis of Human Development Index in West Java: Education and Health Approach - Silviana Luqman; Wedi Rusmawan; Diana Sari; Nuryaman Nuryaman; Achmad Fadjar; Rita Yuniarti; Gedizza Fillah; Zakiah Annisha (LP3M Universitas Putra Bangsa, 2023)
Research Objectives to analyze and determine the West Java Human Development Index (HDI) in the field of health and education. Types of Quantitative Descriptive Research. Research Subject of West Java Province. Observation period 2017-2019. The results showed that the HDI of education was still in the medium category, in line with the performance of the health service performance that showed that it was not effective. For HDIs the health sector gets a very high category, although it has gotten a very high category, there are still targets that have not been achieved. So it is necessary to evaluate and follow up for improvement and, always evaluate what driver the achievements. Always do a review to evaluate the achievement at the end of the year, to assess the success that has been realized, and to detect causes the target has not been achieved.